Methods of analysis of output data for truck engine diagnostics (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The article presents a new method for solving the scientific and practical problem of forming a functional dependence for determining methods of analyzing the initial data of diagnosing truck engines. Applied methods and means of studying the initial data of diagnosing truck engines have been developed, which allow minimizing the resource characteristics at the early stages of product design and modernization. In the course of the research, a method of setting the spatial impact is presented, which consists in the fact that statistical characteristics using known methods are converted into mutual characteristics taking into account the correlation of profiles. At the same time, accounting for the initial data allows for the process of forming the efforts that fall on each parameter of the technical condition of the truck engine and to bring it as close as possible to the real one.
Keywords: data network; diagnostics; truck; method